Advances in the neurorehabilitation of severe disorder of consciousness - Giuliano Dolce; Lucia Francesca Lucca; Francesco Riganello; Francesco Arcuri; Maria Quintieri; Maria Daniela Cortese; Loris Pignolo (Istituto Superiore di Sanità, 2014)
Introduction. The paper describes the evolution of knowledge concerning severe brain injury which determines the Vegetative State/Unresponsive Wakefulness Syndrome. Background. The term Vegetative State was proposed by Jennet and Plum in 1972. Later on, the Intensive Care Units progresses increased the survival of these patients and, contemporary, decreased their characteristic conditions of cachexia and severe dystonia. In 1994, the disease was conceived as a disconnection syndrome of the hemispheres from the brainstem, mainly due to a temporary or permanent deficit of the functions of the white matter. From 2005 on, the psychophysiological parameters relative to an emotional consciousness, albeit submerged, were described. Since then, it has been recognized that the brain of these patients was not only to be considered living but also working. Conclusion. The latest studies that have greatly improved the knowledge of the physiopathology of this particular state of consciousness. These new insights have led to the formation of a European Union Task Force, which has proposed in 2009 to change the name from a Vegetative State to Unresponsive Wakefulness Syndrome, outlining the character of syndrome and not that of state, as forms of even late recovery in consciousness levels have been observed and described.